2017
DOI: 10.1177/0013124517715066
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Neighborhood Poverty on Math Achievement: Evidence From a Value-Added Design

Abstract: Two trends play an increasing role in shaping the long-term prospects of children across the United States: a growing STEM (science, technology, engineering, and mathematics)-based economy and rising income segregation. Together, they suggest that the future well-being of U.S. children may be based increasingly on the contemporary interplay of mathematical learning and neighborhood environments. Drawing on data from the Panel Study of Income Dynamics and a value-added design, this article provides a rigorous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 35 publications
0
21
0
2
Order By: Relevance
“…In the decades that followed, an outburst of scholarship emerged that endeavored to test the hypothesis that living in a high-poverty neighborhood was detrimental to children's academic achievement (Aaronson, 1997;Brooks-Gunn, Duncan, & Aber, 1997;Brooks-Gunn, Duncan, Klebanov, & Sealand, 1993;Jencks & Mayer, 1990;Leventhal & Brooks-Gunn, 2000;Plotnick & Hoffman, 1995;Sampson, Morenoff, & Gannon-Rowley, 2002;Sampson, Sharkey, & Raudenbush, 2008). Indeed, this scholarly fascination with the educational impacts of high poverty neighborhoods and the associated disadvantages contained therein has continued to the present (Crowder & South, 2011;Duncan, Boisjoly, & Harris, 2001;Johnson, 2010Johnson, , 2012Johnson, , 2014Pearman, 2017;Sampson et al, 2008;Sharkey & Elwert, 2011;Wodtke, Elwert, & Harding, 2016;Wodtke, Harding, & Elwert, 2011). Considered in its entirety, this body of scholarship, which became part of the so-called neighborhood effects tradition, has revealed that growing up in a high-poverty neighborhood has an adverse effect on children's educational outcomes beyond that of growing up in an economically disadvantaged family (see Durlauf, 2004;Ellen & Turner, 2003;Sastry, 2012;Sharkey & Faber, 2014, for comprehensive reviews of this literature).…”
mentioning
confidence: 99%
“…In the decades that followed, an outburst of scholarship emerged that endeavored to test the hypothesis that living in a high-poverty neighborhood was detrimental to children's academic achievement (Aaronson, 1997;Brooks-Gunn, Duncan, & Aber, 1997;Brooks-Gunn, Duncan, Klebanov, & Sealand, 1993;Jencks & Mayer, 1990;Leventhal & Brooks-Gunn, 2000;Plotnick & Hoffman, 1995;Sampson, Morenoff, & Gannon-Rowley, 2002;Sampson, Sharkey, & Raudenbush, 2008). Indeed, this scholarly fascination with the educational impacts of high poverty neighborhoods and the associated disadvantages contained therein has continued to the present (Crowder & South, 2011;Duncan, Boisjoly, & Harris, 2001;Johnson, 2010Johnson, , 2012Johnson, , 2014Pearman, 2017;Sampson et al, 2008;Sharkey & Elwert, 2011;Wodtke, Elwert, & Harding, 2016;Wodtke, Harding, & Elwert, 2011). Considered in its entirety, this body of scholarship, which became part of the so-called neighborhood effects tradition, has revealed that growing up in a high-poverty neighborhood has an adverse effect on children's educational outcomes beyond that of growing up in an economically disadvantaged family (see Durlauf, 2004;Ellen & Turner, 2003;Sastry, 2012;Sharkey & Faber, 2014, for comprehensive reviews of this literature).…”
mentioning
confidence: 99%
“…Este es el caso de las personas que viven en zonas rurales y pertenecen a grupos étnicos indígenas, cuyos hijos asisten a escuelas del sistema educativo indígena, y no a una escuela privada o a una escuela urbana regular; estas personas se encuentran incluso en una situación constante de exposición a segregaciones económicas y demográficas que perpetuarán las brechas educativas atribuibles a variaciones del entorno en el que residen (Reardon et al, 2017), por encima de las características individuales, familiares y escolares (Pearman, 2017).…”
Section: Discussionunclassified
“…De esta manera, la baja condición socioeconómica afecta las oportunidades de aprendizaje al reducir drásticamente las posibilidades de elección de la escuela por parte de los padres, y de contar con apoyo académico suplementario y materiales educativos adicionales, profundizando la inequidad educacional (Caro y Lenkeit, 2012;Olszewski-Kubilius y Corwith, 2018). Según Pearman (2017), la exposición constante a asentamientos humanos de alta pobreza tiene un efecto negativo en el rendimiento en matemáticas más allá del asociado a las características individuales, familiares y escolares. Por el contrario, los alumnos de condiciones socioeconómicos y culturales más favorecidos "poseen desde el inicio puntajes más altos que los demás y presentan pendientes de crecimiento más empinadas" (Muelle, 2020, p.136).…”
Section: Introducción Contexto Sociodemográfico Y Logro Académicounclassified
“…Then they estimated school and neighborhood contributions to 1-year gains in student test scores for elementary and middle school without considering performances within students’ grades, as described above. More recently, Pearman (2019) estimated the effects of neighborhood poverty across children up to age 12. Specifically, Pearman tested the hypothesis that exposure to high-poverty neighborhoods influenced students’ mathematical proficiency over and above their individual and school characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%